On the transitory performance of mixed convective heat and mass transfer around spherical region in the presence of fluctuating streams - Hossam A. Nabwey; Sahar Anwar; Muhammad Ashraf; A.M. Rashad (Case Studies in Thermal Engineering)
The core intention of this novel study is to scrutinize the mixed convective fluid flow at distinct locations around a sphere with fluctuating streams of velocity, heat, and mass. This mechanism of heat and mass transfer is of great importance in thermal management systems, biomedical technology, and particle dispersion in environmental flows with many others. It also offers a great understanding of predicting the pollutant and heat spread in the environment. Further, this mechanism will help to observe the steady as well as oscillating nature of the fluid flow around a sphere. For this purpose, the coupled partial differential equations are first non-dimensionalized and their steady and oscillatory components are separated. Then these are transformed into more manageable forms via appropriate primitive variable formulation. To obtain the computational solution, the transformed equations are discretized by employing the FDM (Finite Difference Method). The obtained results for the Prandtl number Pr, Schmidt number Sc, mixed convection parameter λT and modified mixed convection parameter λC are illustrated in graphical format at different locations at X=0.1,1.5 and π radian for both steady and transient flow and tabular form for the steady flow. The fluid's velocity in steady flow achieved its peak value at the location X=1.5 rad while mass and temperature distribution attained their maximum at the location X=0.1 rad for all the parameters. The skin friction with the transport rates of energy and mass dropped for ascending values of λT and λC at location X=1.5 rad. For the fluctuating unsteady part, the transient skin friction has an adequately smaller oscillation amplitude at distinct locations for all parameters. The transient rate of heat transport has a higher amplitude and increasing trend for incrementing Pr and Sc. Whereas, the transient rate of mass transport exhibits a rising trend for Pr and λC at specified locations.